COMPARATIVE MORPHOLOGICAL ANALYSIS OF E-COMMERCE TERMS IN ENGLISH AND UZBEK LOGISTICS DISCOURSE - Tukhtasinova Zarina (Prospects for innovative technologies in science and education, 2025)
This article analyzes the morphological structure of terms related to the fields of e-commerce and logistics in English and Uzbek. As a result of globalization and the development of digital technologies, new terms that have emerged in these areas are actively entering the language system. The study examines how the analytical structure of the English language and the agglutinative structure of the Uzbek language affect the formation and assimilation of e-commerce terms.